Analisis Kelayakan Pengembangan Usaha Pengolahan Kerupuk Ikan Lele Clipss Catfish Chips Di Kota Bogor (Forum Agribisnis, 2020)
Catfish cracker processing business has enormous potential to be developed for several reasons, namely the high supply of catfish, the lack of utilization of catfish supply, and the increasing consumption trend of crackers. Clipss Catfish Chips is a catfish cracker processing business whose business development plan in the form of increasing production capacity includes the procurement of production machinery and relocation of the production house. Clipss Catfish Chips will also conduct business legalities to support the business development process. This research was conducted to assess the long-term investment planning on the development plan that Clipss will do. Data processing and analysis used in this research include feasibility analysis of non-financial aspects and financial aspects and switching value analysis. Analysis of non-financial aspects was studied qualitatively with descriptive and quantitatively with a Likert scale. Analysis of the financial aspect was studied using a few investment criteria namely Net Present Value, Net Benefit-Cost Ratio, Internal Rate of Return, and Payback Period. The results of the feasibility analysis of non-financial and financial aspects indicate that business development is feasible to run. The results of the switching value analysis show that the decrease in the amount of production is more sensitive than the increase in the price of fish and packaging.